(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: To assess the quality of recovery and satisfaction with postoperative pain control and anesthesia, and to describe some factors influencing hospital recovery. Subjects and methods: This was a cross-sectional descriptive study involving postoperative patients aged 18 years or older, who were hospitalized for at least 24 hours at Vinmec Nha Trang International Hospital between May 2024 and May 2025. A total of 897 patients were surveyed using the QoR-15 scale (Vietnamese version, translated and validated). Results: The mean QoR-15 score was 141.2 ± 10.79, indicating a good level of recovery. A total of 92.3% of patients reported recovery levels ranging from “good” to “excellent.” Satisfaction with postoperative pain control was high, with 94.1% of patients rating it 9–10. Type of anesthesia (p < 0.05) and length of stay in the Post-Anesthesia Care Unit (PACU) (p < 0.05) significantly affected recovery scores and patient satisfaction. Local anesthesia and PACU stay under 60 minutes were associated with better recovery outcomes. Conclusions: The QoR-15 scale demonstrated high reliability (Cronbach’s alpha = 0.891) and practical applicability in evaluating postoperative recovery. Optimizing anesthetic techniques and minimizing PACU stay duration may improve care quality and patient satisfaction. Further research is recommended across multiple healthcare settings and diverse patient populations to validate these findings.